P1 gene of Mycoplasma pneumoniae isolated from 2016 to 2019 and relationship between genotyping and macrolide resistance in Hokkaido, Japan. Issue 6 (24th June 2021) - Ishiguro, Nobuhisa; Sato, Rikako; Kikuta, Hideaki; Nakanishi, Masanori; Aoyagi, Hayato; Mori, Toshihiko; Nagano, Naoko; Tabata, Yuichi; Hazama, Kyosuke; Konno, Mutsuko; Yamanaka, Tatsuru; Azuma, Katsumi; et al.
Abstract : We characterized 515 Mycoplasma pneumoniae specimens in Hokkaido. In 2013 and 2014, the p1 gene type 1 strain, mostly macrolide-resistant, was dominant and the prevalence of macrolide resistance was over 50 %. After 2017, the p1 gene type 2 lineage, mostly macrolide-sensitive, increased and the prevalence of macrolide resistance became 31.0 % in 2017, 5.3 % in 2018 and 16.3 % in 2019.